Current Trends in Pediatric Minimally Invasive Urologic Surgery - Lee, Dennis J. (The Korean Urological Association, 2010)
Over the past two decades, laparoscopic and robotic surgery in children has been described as a viable minimally invasive alternative to open surgery for many pediatric urologic conditions. With the goal of reducing the morbidity associated with open surgery, minimally invasive surgery in children is increasingly being performed as laparoscopic and robotic patients appear to be experiencing shorter hospital stays, decreased pain medication requirements, and the potential for improved cosmesis. This article provides an overview of the existing literature in laparoscopic and robotic-assisted laparoscopic urologic surgery in children. Laparoscopic and robotic-assisted laparoscopic surgery appears to be safe and effective in children for a wide range of ablative and reconstructive procedures. Conventional laparoscopic surgery is effective for ablative procedures, while robotic surgery may be ideally suited for reconstructive cases requiring advanced suturing and dissection. Overall, more prospective studies are needed to study the long-term outcomes of minimally invasive surgery in pediatric patients, and the appropriate use of the available technology.